Empirical Evidences Of Customer Satisfaction A Study Of Mobile Banking Services (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Technology has played a vital role in the evolution of Indian banking  sector through speed, accuracy, efficiency, promptness and reduction in  cost. Banking services are now tilting to “Anywhere Anytime banking”  aspect. Today banks are providing services through different automated  channels like ATM, Debit Card, Credit Cards, Internet Banking, Mobile  Banking, Phone Banking, RTGS, NEFT and ECS etc. Mobile banking is  a system of providing services to the customers to carry out banking  transactions on the 'Mobile Phone' through a cellular service provider.  Mobile Banking is gaining increasing acceptance amongst various  sections of the society. The objective of the proposed paper is to study the  customer satisfaction towards mobile banking services provided by  various banks operating in Delhi and NCR. To achieve the objective of  the study, primary data was collected through a structured questionnaire from the respondents using mobile banking services  (public, private and foreign banks). In total, 187 respondents were  studied with the help of a convenience sampling method. To analyze the  collected data, SPSS version 19 was used. The various statistical  techniques used for analysis and achieve the objectives of the study are  frequency distribution along with percentages, mean, standard  deviation. To test the null hypothesis, parametric tests such as t test and  ANOVA was used. The major findings of the study reflected that 'sector  of the banks', 'occupation of respondents' and 'age of the respondents'  has significant impact on customer satisfaction. The study provides  meaningful direction to bank managers and decision makers to improve  their service quality for higher customer satisfaction.
Keywords: Indian Banking; Primary data; Customer Satisfaction; Mobile Banking Services and Information and Technology